Güneşten korunma programının adölesanların güneşten korunma davranışlarına etkisi: transteoretik modele dayalı bir çalışma - Aygün, Özcan (My University, 2013)
1. ÖZET Bu çalışma, güneşten korunma programının (GKP) adölesanların güneşten korunma davranışlarına etkilerinin araştırılması amacıyla ön-son-izleme test ve kontrol gruplu yarı deneysel bir tasarım olarak gerçekleştirildi. Çalışma, Sakarya’da bulunan iki özel okulun 6. ve 7. sınıflarında öğrenim gören toplam 180 adölesan ile yürütüldü (girişim grubu: 96, kontrol grubu: 84). Veriler Transteoretik model (TTM) güneşten korunma ölçekleri ile toplandı. Okul temelli uygulanan GKP’nin girişim grubunda son testte orta düzeyde etkili olduğu, izlemde ise etkisinin olmadığı saptandı. GKP’nin, girişim grubundaki öğrencilerin güneş yanığı oranını azaltmada etkili olduğu, güneşten kaçınma ve güneş koruyucu kullanma davranışları ve

yeterliliklerinin olumlu yönde değişmesine katkı sağladığı belirlendi (p<.05). Son testte girişim grubundaki öğrencilerin TTM güneşten korunma ve güneş koruyucu kullanma değişim aşamalarında kontrol grubuna göre istatistiksel olarak anlamlı ilerlemeler saptandı (p<.05). Öğrencilerin bilgi puanları, güneşten korunma yarar ve zarar algılarında girişim ve kontrol grupları arasında istatistiksel olarak anlamlı farklılık saptanmadı (p>.05). Girişim grubundaki erkek öğrencilerin güneşten korunma davranışları ve öz yeterliliklerinin kontrol grubundan istatistiksel olarak anlamlı yüksek olduğu belirlendi. Kızlarda ise sadece son testte girişim grubunun güneşten kaçınma öz yeterliliği kontrol grubundan istatistiksel olarak anlamlı yüksekti (p<.05). Çalışmanın sonuçları ışığında, güneşten korunma korunma programının adölesanlar üzerindeki etkilerinin daha sağlıklı değerlendirmesinde aile katılımlı, daha uzun süreli ve yaz döneminde sürdürülen çalışmaların planlanması önerilebilir. Ek bir öneri olarak GKP’nin kız öğrenciler üzerine etkisini arttıracak ileri çalışmalar gereklidir. Transteoretik model, güneşten korunma, güneş koruyucu, adölesan, cilt kanseri önleme. 2. SUMMARY THE EFFECT OF A SUN PROTECTION PROGRAM ON THE SUN-PROTECTION BEHAVIOR OF ADOLESCENTS: A STUDY BASED ON THE TRANSTHEORETICAL MODEL, This study was of a semi-experimental research design and used pre-post and follow-up tests with controls to explore the effects of a sun protection program (SPP) on the sun-protection behavior of adolescents. The research was conducted with a total of 180 adolescents enrolled in the 6th and 7th grades of two private schools in the province of Sakarya (intervention group: 96; control group: 84). The data were collected with sun protection scales based on the Transtheoretical Model (TTM). It was found on the post-test that the school-based application of the SPP was moderately effective in the intervention group and had no effect in the follow-up. It was determined that the SPP was effective in reducing the rate of sunburn in students in the intervention group, that it contributed to a change in behavior that ensured avoiding the sun and using sun protection methods, and also resulted in a positive change in self-efficacy (p<.05). It was found that in the post-test, compared to the control group, there was more significant progress in the students in the intervention group in terms of TTM stages of behavioral change concerning sun protection and using sun protection methods (p<.05). No significant differences however were discovered between the intervention and control groups in terms of the students' knowledge scores and their perceptions of the benefit and harm of exposure to the sun (p>.05). It was found that the boys in the intervention group scored significantly higher in sun protection behavior and self-efficacy compared to the control group. Among the girls, the scores for self-efficacy in terms of avoiding the sun was significantly higher in the post-test of the intervention group than in the control group (p<.05). In the light of the results of the study, it might be suggested that more studies and research of longer duration that also involves student families be planned for the summertime so that more reliable conclusions regarding the effects of a sun protection program on adolescents can be obtained. An additional recommendation would be that more advanced studies be conducted to increase the effect of the SPP on girls. Key words: Transtheoretical model, sun protection, sunscreen, adolescent, skin cancer prevention.
Keywords: Halk Sağlığı